2010
DOI: 10.1111/j.1365-2605.2010.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Second to fourth digit ratios, male genital development and reproductive health: a clinical study among fertile men and testis cancer patients

Abstract: Second- to fourth-digit length ratio, 2D:4D, is a marker of testosterone level during foetal life that was found associated with sperm concentration or testosterone levels in some studies, but not in others, a difference possibly related to the way the ratio is assessed. In this study, 2D:4D was assessed in 122 men partners of pregnant women and in 71 testicular cancer patients using a new method based on direct measurements of finger lengths. In addition, we investigated the association between 2D:4D, birth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
7
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 55 publications
3
44
7
1
Order By: Relevance
“…The largest study to date, which included 360 young men from a normal population, found no relationship of 2:4 digit length ratio with testis or semen parameters [20]. Other studies showed significant negative associations between 2:4 digit length in men and reproductive success; in those studies, the 2:4 digit length ratio was higher in infertile men than in fertile men [21,22]. There are no reports on the relationship between the 2:4 digit length ratio and the occurrence of cryptorchidism or hypospadias.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study to date, which included 360 young men from a normal population, found no relationship of 2:4 digit length ratio with testis or semen parameters [20]. Other studies showed significant negative associations between 2:4 digit length in men and reproductive success; in those studies, the 2:4 digit length ratio was higher in infertile men than in fertile men [21,22]. There are no reports on the relationship between the 2:4 digit length ratio and the occurrence of cryptorchidism or hypospadias.…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates a female preference for men with a low 2D:4D ratio possibly driven by the fact that these have more symmetrical faces. Such a preference might have evolved because it increases females' reproductive success by gaining benefits from partners who are physically more robust [1] and who have more fertile ejaculates [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is that also digit ratios are related to endocrine exposure (Zheng and Cohn, 2011). However, no indication for hormone disruption with this specific read out in relationship with development of GCC has been found so far (Auger and Eustache, 2011). However, such a link was found based on measurements of steroid hormone during early pregnancy (Holl et al, 2009).…”
Section: Epidemiology and Risk Factors Of Human Gccmentioning
confidence: 99%